Relationship between attendance at childbirth preparation classes and fear of childbirth and type of delivery - Fatemeh Najafi; Kobra Abouzari-Gazafroodi; Fatemeh Jafarzadeh-Kenarsari; Parvin Rahnama; Bahare Gholami Chaboki (Tehran University of Medical Sciences, 2016)
Background & Aim: Maternal request for caesarean section due to fear of normal vaginal delivery (NVD) is one of the main reasons for the high rate of caesarean section. This study aimed to compare the fear of NVD and type of delivery between two groups of pregnant women attended childbirth preparation classes (CPC) and women received routine prenatal care (RPC). Methods & Materials: In this prospective cohort study, 202 Primigravid women attended healthcare centers for prenatal care services in the East of Guilan were selected using convenient sampling in 2013-2014. Fear of NVD was assessed using a childbirth attitude questionnaire at two stages (before attending CPC or receiving RPC, then at the third trimester of pregnancy). Both groups were followed up to the delivery time. Data were analyzed using inferential and descriptive statistics (Chi square, paired t-test, ANOVA, t-test) through SPSS v.16. P<0.05 was considered as significant. Results: There was no significant difference (P=0.23) in the mean score of fear of NVD between two groups before attending CPC (35.59±8.78) and receiving RPC (37.08±9.08). The comparison of the mean score of fear of NVD between two groups at the third trimester of pregnancy showed a significant reduction (P<0.001) in the first group (32.30±8.31) than in the second group (37.29±9.55). A significant difference was also observed between two groups in the rate of NVD (P=0.002). Conclusion: Results confirm the importance of CPC in decreasing fear of NVD and increasing the rate of NVD in primigravid women attended these classes. Therefore, women's attendance at CPC is recommended to be encouraged.